Deglaciation and meltwater events in Hudson Strait and the Eastern Canadian Arctic - Andrews, J. T.; Matthews, R. K.; Osterman, L. E.; Miller, G. H.; Hillaire-Marcel, C.; Williams, K. M. (Geo-Marine Letters, 1987)
Stable isotope measurements on molluses from raised marine deposits, and on foraminifera in a piston core, define a series of light isotope events. A major event is14C dated at ca. 10.3 ka and is correlated with a marked isotopic excursion in HU77-021-156. This event is followed by a dramatic rise in diatom and, slightly later, in benthic foraminiferal abundances. Molluses record another light event around 8 ka. Major fluctuations in both δ18O and δ13C around 10.3 ka suggests that the Hudson Strait ice stream may have responded to the Younger Dryas climatic oscillation.